A systematic review examining the relationship between cytokines and cachexia in incurable cancer. Issue 2 (25th January 2022) - Paval, D. Robert; Patton, Rebekah; McDonald, James; Skipworth, Richard J.E.; Gallagher, Iain J.; Laird, Barry J.; ,
Abstract: Cancer cachexia is an unmet clinical need that affects more than 50% of patients with cancer. The systemic inflammatory response, which is mediated by a network of cytokines, has an established role in the genesis and maintenance of cancer as well as in cachexia; yet, the specific role of the cytokine milieu in cachexia requires elucidation. This systematic review aims to examine the relationship between cytokines and the cachexia syndrome in patients with incurable cancer. The databases MEDLINE, EMBASE, CINAHL, CENTRAL, PsycINFO, and Web of Science were searched for studies published between 01/01/2004 and 06/01/2020. Included studies measured cytokines and their relationship with cachexia and related symptoms/signs in adults with incurable cancer. After title screening ( n  = 5202), the abstracts ( n  = 1264) and the full‐text studies ( n  = 322) were reviewed independently by two authors. The quality assessment of the selected papers was conducted using the modified Downs and Black checklist. Overall, 1277 patients with incurable cancer and 155 healthy controls were analysed in the 17 eligible studies. The mean age of the patients was 64 ± 15 (mean ± standard deviation). Only 34% of included participants were female. The included studies were assessed as moderate‐quality to high‐quality evidence (mean quality score: 7.8; range: 5–10). A total of 31 cytokines were examined in this review, of which interleukin‐6 (IL‐6, 14 studies) and tumour necrosis factor‐α (TNF‐α, 12 studies) were the most common. The definitions of cachexia and the weight‐loss thresholds were highly variable across studies. Although the data could not be meta‐analysed due to the high degree of methodological heterogeneity, the findings were discussed in a systematic manner. IL‐6, TNF‐α, and IL‐8 were greater in cachectic patients compared with healthy individuals. Also, IL‐6 levels were higher in cachectic participants as opposed to non‐cachectic patients. Leptin, interferon‐γ, IL‐1β, IL‐10, adiponectin, and ghrelin did not demonstrate any significant difference between groups when individuals with cancer cachexia were compared against non‐cachectic patients or healthy participants. These findings suggest that a network of cytokines, commonly IL‐6, TNF‐α, and IL‐8, are associated with the development of cachexia. Yet, this relationship is not proven to be causative and future studies should opt for longitudinal designs with consistent methodological approaches, as well as adequate techniques for analysing and reporting the results.